2005
DOI: 10.1109/tbme.2005.857636
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Joint Symbolic Dynamics of Heart Rate and Blood Pressure in Dilated Cardiomyopathy

Abstract: Abstract-Autonomic cardiovascular control involves complex interactions of heart rate and blood pressure. In patients with dilated cardiomyopathy (DCM), this control is impaired and parameters for its quantification might be of prognostic importance. In this paper, we introduce methods based on joint symbolic dynamics (JSD) for the enhanced analysis of heart rate and blood pressure interactions. To assess the coarse-grained dynamics beat-to-beat changes of heart rate and blood pressure are encoded in symbol st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 22 publications
1
41
0
Order By: Relevance
“…The concept of symbolic dynamics allows for an easy interpretation of physiological data by a simplified description of the system's dynamics and offers a framework for exploring the nature of a system through a means of simplified analysis. 2,5,6,30,49 By employing a coarse-graining procedure some of the time series' detailed information is lost while the robust properties of the dynamics are preserved. 6,49 In this article, we introduce a novel approach to quantify cardiorespiratory interaction that is based on the joint symbolic dynamics of respiratory phase and heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of symbolic dynamics allows for an easy interpretation of physiological data by a simplified description of the system's dynamics and offers a framework for exploring the nature of a system through a means of simplified analysis. 2,5,6,30,49 By employing a coarse-graining procedure some of the time series' detailed information is lost while the robust properties of the dynamics are preserved. 6,49 In this article, we introduce a novel approach to quantify cardiorespiratory interaction that is based on the joint symbolic dynamics of respiratory phase and heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…For the analyses of the physiological regulatory systems (cardiovascular, cardiorespiratory) as well as the quantification of their interactions, a variety of linear as well as nonlinear methods ranging from parametric models in the time-or in the frequency domain to model-free approaches in the information domain have been proposed [71]. Linear methods are partly insufficient to quantify nonlinear structures and the complexity of physiological systems (time series)-the joint symbolic dynamics (JSD) [4,72] and high resolution joint symbolic dynamics (HRJSD) [73] overcomes the limitations.…”
Section: Symbolic Dynamicsmentioning
confidence: 99%
“…(1) (2) Here, Th represents a defined threshold value which allows distinguishing high beat-to-beat variability from small changes that might be within the noise floor. For this study Th=2 was used.…”
Section: Joint Symbolic Dynamicsmentioning
confidence: 99%
“…Compared to conventional signal-processing approaches which are inadequate for characterizing complex system dynamics, joint symbolic dynamics (JSD) has been shown to be an effective technique to provide enhanced information by employing a coarse-graining procedure to preserve the robust properties of the system's complex dynamics [2,3]. Symbolic dynamics has been widely used to study HRV dynamics and is suggested to provide improved performance for the analysis of respiratory data and cardiorespiratory interaction [3,4].…”
Section: Introductionmentioning
confidence: 99%